19 Complications Associated with Cardiac Resynchronisation Therapy Upgrades Versus De Novo Implants: 3-Year Experience at a Regional Pacing Centre. (31st May 2014) - James, Simon; Turley, Andrew; Dewhurst, Matthew; Shome, Joy; Lee, David; Phan, Thanh; Thornley, Andrew; Linker, Nicholas
Abstract : Introduction: Indications for cardiac resynchronisation therapy (CRT) are expanding; included in this are patients with symptomatic heart failure and chronic right ventricular pacing undergoing upgrade procedures. Previously reported data from the REPLACE registry suggest a much higher complication rate (18.7% overall) associated with CRT upgrade procedures than data regarding de novo implants. We report our 3 year experience at a regional pacing centre in North-East England. Methods: We undertook a retrospective observational study in a UK tertiary pacing centre. We reviewed the electronic hospital records and pacing files of 183 consecutive patients who underwent their first attempted CRT implantation between January 1 st 2010 and December 31 st 2012. We compared de novo implants with upgrade procedures, recording all documented complications up to the most recent device clinic follow-up. Significance of between group differences were calculated using Fisher's 2-tail test. Results: Conclusions: Our data compares favourably to previously reported data in terms of overall complication rates of LV lead implantation. What we found striking was that complication rates for upgrade procedures were not significantly different to de novo implants and may be because over a third (35%) of our CRT procedures are upgrades.